(untitled) (Medical Forum Monthly, 2024)
Objective: To determine vitamin D levels in newly diagnosed cases of multiple myeloma and to determine effects of vitamin D supplementation using laboratory parameters on outcome of the disease. Study Design: Comparative study. Place and Duration of Study: This study was conducted at the Haematology Department of Shaikh Zayed Hospital, Lahore and INMOL Hospital, Lahore from January to June 2018. Materials and Methods: Thirty two patients of multiple myeloma were included in the study and were divided into two equal groups A and B. Baseline laboratory parameters;vitamin D, β2 microglobulin and serum albumin levels were performed. Patients in group A were given vitamin D supplementations along with standard myeloma chemotherapy. Whereas patients in group B were without adjuvant vitamin D supplementation. Laboratory parameters in both groups were repeated and compared at 12 and 18 weeks follow-up. Results: At baseline, mean vitamin D level in group A was 17.86 ± 14.23 ng/ml and in group B was 25.95 ± 15.89 ng/dl. At 18th week follow-up, mean vitamin D level in group A was 44.14 ± 20.99 ng/ml and in group B was23.92 ± 14.11 ng/dl, which was statistically significant (p-value 0.003).Comparison of mean β2 microglobulin and albumin levels between the two groups were found insignificant at 18th week follow-up.To determine the effect of vitamin D supplementation on outcome of multiple myeloma, hypothetical scoring was calculated and compared between the two groups which was found statistically insignificant. Conclusion: Significant low vitamin D levels (78.12%) had been found in multiple myeloma. There was significant improvement of vitamin D levels with oral supplementations, but laboratory parameters alone has shown no significant results at short term follow-up.